Immunological and bacteriological monitoring of periodontal tissue in pregnancy = Monitoreo inmunológico y bacteriológico de los tejidos periodontales en el embarazo - Solari, Natalia; Salas, Leonardo; Tabares, Sandra; Rosella, Carolina; Matilde Usin, María (2023)
We determine periodontal pathogens in periodontal pockets from pregnant women with periodontitis and associate it to the C reactive protein (CRP), nitrates, immunoglobulin A and G (Ig A and G), and myeloperoxidase (MPO) levels in saliva to identify some biomarkers as tools to predict the periodontal status from pregnant. The samples were obtained from periodontal pockets and saliva from 100 pregnant women (PW) and 50 non-pregnant women (NPW). Every patient was evaluated by: 1) probing depth (PD) and loss of clinical attachment level (CAL); 2) in saliva; CRP, MPO, Ig A and G) and nitrite concentrations, 3) in periodontal pockets: P.gingivalis, T.forsythia, T.denticola, P.intermedia, A.actinomycetemcomitans. InfoStat/P 2008 software was used with a p-value <0.05. Clinical parameters showed stages I and II of PD in both groups. P.intermedia and A.actinomycetemcomitans were observed only in periodontal pockets from PW. The CAL was higher in pregnant of the 3rd trimester than in the other stages and was associated with low levels of IgA and the presence of P.intermedia and T. forsythia in the same trimester. The levels of IgA in saliva would reflect the immunological situation in pregnant women. This could be used to monitor the immune status of the gingival tissues during pregnancy.
Determinamos patógenos periodontales en bolsas periodontales de gestantes con periodontitis y lo asociamos a los niveles de proteína C reactiva (PCR), nitratos, inmunoglobulina A y G (Ig A y G) y mieloperoxidasa (MPO) en saliva para identificar biomarcadores como herramientas para predecir el estado periodontal de la gestante. Las muestras se obtuvieron de bolsas periodontales y saliva de 100 mujeres embarazadas (ME) y 50 mujeres no embarazadas (NoE). Cada paciente fue evaluado por: 1) profundidad de sondaje(PD) y pérdida del nivel de inserción clínica (NIC); 2) en saliva; PCR, MPO, Ig A y G y concentraciones de nitritos, 3) en bolsas periodontales: P.gingivalis, T.forsythia, T.denticola, P.intermedia, A.actinomycetemcomitans. Se utilizó el software InfoStat/P 2008 con un valor de p<0,05. Los parámetros clínicos mostraron estadios I y II de EP en ambos grupos. P.intermedia y A.actinomycetemcomitans se observaron solo en bolsas periodontales de ME. El NIC fue mayor en gestantes del 3er trimestre que en las demás etapas y se asoció con niveles bajos de IgA y presencia de P.intermedia y T.forsythia en el mismo trimestre. Los niveles de IgA en saliva reflejarían la situación inmunológica en la mujer embarazada. Esto podría usarse para monitorear el estado inmunológico de los tejidos gingivales durante el embarazo.
En revista Odóvtos, vol. 25, no.2 (mayo-agosto 2023)
Descripción basada en el contenido visto el 17 de diciembre, 2024
También disponible en formato HTML y EPUB